Corn oil supplementation enhances hydrogen use for biohydrogenation, inhibits methanogenesis, and alters fermentation pathways and the microbial community in the rumen of goats - Xiumin Zhang; Medrano, Rodolfo F.; Min Wang; Beauchemin, Karen A.; Zhiuuan Ma; Rong Wang; Jiangnan Wang; Lukuyu, Ben A.; Tan, Zhi Liang; Jian Hua He (Oxford University Press, 2019)
Enteric methane (CH4) emissions are not only an important source of greenhouse gases but also a loss of dietary energy in livestock. Corn oil (CO) is rich in unsaturated fatty acid with >50% PUFA, which may enhance ruminal biohydrogenation of unsaturated fatty acids, leading to changes in ruminal H2 metabolism and methanogenesis. The objective of this study was to investigate the effect of CO supplementation of a diet on CH4 emissions, nutrient digestibility, ruminal dissolved gases, fermentation, and microbiota in goats. Six female goats were used in a crossover design with two dietary treatments, which included control and CO supplementation (30 g/kg DM basis). CO supplementation did not alter total-tract organic matter digestibility or populations of predominant ruminal fibrolytic microorganisms (protozoa, fungi, Ruminococcus albus, Ruminococcus flavefaciens, and Fibrobacter succinogenes), but reduced enteric CH4 emissions (g/kg DMI, −15.1%, P = 0.003). CO supplementation decreased ruminal dissolved hydrogen (dH2, P < 0.001) and dissolved CH4 (P < 0.001) concentrations, proportions of total unsaturated fatty acids (P < 0.001) and propionate (P = 0.015), and increased proportions of total SFAs (P < 0.001) and acetate (P < 0.001), and acetate to propionate ratio (P = 0.038) in rumen fluid. CO supplementation decreased relative abundance of family Bacteroidales_BS11_gut_group (P = 0.032), increased relative abundance of family Rikenellaceae (P = 0.021) and Lachnospiraceae (P = 0.025), and tended to increase relative abundance of genus Butyrivibrio_2 (P = 0.06). Relative abundance (P = 0.09) and 16S rRNA gene copies (P = 0.043) of order Methanomicrobiales, and relative abundance of genus Methanomicrobium (P = 0.09) also decreased with CO supplementation, but relative abundance (P = 0.012) and 16S rRNA gene copies (P = 0.08) of genus Methanobrevibacter increased. In summary, CO supplementation increased rumen biohydrogenatation by facilitating growth of biohydrogenating bacteria of family Lachnospiraceae and genus Butyrivibrio_2 and may have enhanced reductive acetogenesis by facilitating growth of family Lachnospiraceae. In conclusion, dietary supplementation of CO led to a shift of fermentation pathways that enhanced acetate production and decreased rumen dH2 concentration and CH4 emissions.